Synthesis, Characterization, and Application of Magnetite (Fe3O4) Particles as Gold Adsorbent from Simulation Waste - Maya Rahmayanti; Sri Juari Santosa; Sutarno Sutarno; Hilmi Hamidi; Lingga Binagara (Universitas Ahmad Dahlan, 2020)
There have been many magnetic adsorbents in solid phase extraction to recover gold metal known as Magnetic Solid Phase Extraction (MSPE). In this study, magnetite was synthesized using the reverse coprecipitation method with the precipitating agent NaOH. The synthesized material was characterized using a Fourier Transform Infrared (FTIR) spectrophotometer, X-Ray Diffraction (XRD), Vibrating Sample Magnetometer (VSM), and Scanning Electron Microscopy (SEM). The magnetite was then applied as a gold adsorbent from simulated waste (HAuCl4). The effect of acidity on the performance of magnetite as gold adsorbent was studied at various pH ranges. Based on the results of characterization using FTIR, magnetite has been successfully synthesized, marked by the appearance of a typical absorption for Fe-O bonds at a wave number of 578 cm-1. It is amplified with an XRD diffractogram, which gives peaks similar to a standard magnetite diffractogram. The value of the magnetite saturation magnetization was 93.90 emu/g. Based on application studies, [AuCl4] adsorption on magnetite was excellent in the pH range 3-5. The presumed interactions between [AuCl4]- and magnetite were through electrostatic (dipol-ion) interactions, hydrogen bonding, and redox reactions.